POPULATION FLUCTUATION OF ADULT MALES OF THE FRUIT FLY, Bactrocera tau Walker (DIPTERA: TEPHRITIDAE) IN PASSION FRUIT ORCHARDS IN RELATION TO ABIOTIC FACTORS AND SANITATION - A. Hasyim; Muryati Muryati; W.J. de Kogel (Indonesian Agency for Agricultural Research and Development, 2008)
Fruit fly (Bactrocera tau) is the most destructive pest on some fruits in Indonesia. Monitoring of the pest population is essential as one of the procedures in the IPM concept. The study aimed to investigate the seasonal fluctuation of adult males of B. tau and their damage on passion fruits in relation to abiotic factors. The research was done by a survey method on three plots of passion fruit orchards in Alahan Panjang, West Sumatra, Indonesia from March to December 2005. In plot 1 the farmer practiced sanitation by removing damaged fruits and weeds from the orchard. In the plots 2 and 3 no sanitation was practiced. Each plot was 1 ha in size. The parameters observed were density of adult male B. tau and climatic factors (rainfall per day, number of rainy days, and average day temperature). Empty mineral water bottle traps were used to catch adult males of B. tau. Each plot had 16 traps set up with cue lure as fruit fly attractant. Each trap was baited with 3 ml cue lure on a cotton wick (1 cm diameter). The cotton wick was rebaited at 2-week intervals. The traps were placed on host plants about 1.5 m above the ground. Trapped flies were collected every two weeks and counted. The data were analyzed by correlation analysis. The results revealed that the number of male B. tauin three orchards showed a similar fluctuation during the study period with a major peak in July. The lower numbers of flies captured in plot 1 (with sanitation) compared to the two other plots (without sanitation) were consistent with a lower percentage of damaged fruits in the plot 1 compared to the other two. The percentage of damaged fruits gradually decreased over time to about 20% in plot 1 which is lower than that in the other twoplots (30-40%). The number of fruit flies captured with cue lure baited traps correlated positively with all three abiotic factors studied. The seasonal fluctuation of the fruit fly population and the damage to the fruits are necessary to be studied as a procedurein IPM for controlling B. tau.